Analysis of the Torque Transmission Performance of Double 3-RRS Over-redundant Actuation Flight Simulator - Zhou Changchun; Wang Qi (Jixie chuandong)
The torque transmission performance of flight simulator with double 3-RRS over-redundant actuation spherical parallel manipulator is analyzed. The flight simulator has 3 rotational degrees of freedom,6 actuators,3 redundant actuators are included in 6 actuators. Two totally same spherical parallel manipulators consist of the flight simulator. Because of only one fixed coordinate frame is established,it has one fixed base in general and one moving platform. The whole moving platform is served as the flight simulator capsule. The directional cosines of the branch are determined by anti-symmetric coordinates frame,and on this basis,the Jacobian matrix of the over-redundant actuation spherical parallel manipulator is given. The torque transmission performance index of the double and single 3-RRS over-redundant actuation spherical parallel manipulator are analyzed and its atlas of torque transmission performance are given out,and according to the 3D atlas,the analysis conclusion is given.